Implementasi Kebijakan Pemekaran Desa Dalam Penyelenggaraan Pelayanan Publik Di Kecamatan Tompaso Kabupaten Minahasa - Onibala, Nancy Melisa (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT: Proliferation of Regional Rural Policy intensively until now has been developed in Indonesia as one way for equitable development and improve the welfare of society .Historically ,the village is the origin of the formation of political society and government in Indonesia long before this nation was formed . Based on the above authors interested in conducting a study on the implementation of village expansion policy in the administration of public services in the district of Minahasa District Tompaso .The study is titled on the implementation of village expansion policy which aims to improve services public.research aims to describe,analyze and determine the division of policy implementation in public service village in the district of Minahasa regency Tompasowith indicator; Communication, recourcess, Disposition and bureaucracy structure.The research method used was qualitative research using analytical methods Milles Huberman.Berdasarkan research has been done , then the author can draw the conclusion that the expansion policy implementation in rural districts Tompaso going well , although the influence of power and kepentigan actor and implementing compliance and responsiveness somewhat affect the implementation of the program assessed the implementation and facilities are still lacking influence public nature of the service , but the corresponding field interviews deficiency does not prevent the implementation of village expansion policy in the administration of public services in the district Tompaso . Keywords : Implementation of policy , the Village Expansion , Public service